The cookie bible - Beranbaum, Rose Levy (Houghton Mifflin Harcourt, 2021)
"The ultimate cookie cookbook, from best-selling author of The Baking Bible Rose Levy Beranbaum. This is your must-have cookie book, featuring nearly every cookie imaginable, from rustic Cranberry Chocolate Chippers to elegant French macarons, and everything in between--simple drop cookies, rolled-and-cut holiday cookies, brownies and other bars, pretty sandwich cookies, luxurious frosted or chocolate-dipped treats, and much more. With legendary baker Rose Levy Beranbaum's foolproof recipes--which feature detail-oriented instructions that eliminate guesswork, notes for planning ahead, ingenious tips, and other golden rules for success--it's easy to whip up a batch of irresistible, crowd-pleasing cookies anytime, for any occasion. Standout classics and new favorites include: Rose's Dream Chocolate Chip Cookies, Lemon Lumpies, Black Tahini Crisps, Peanut Butter and Jelly Buttons, Double Ginger Molasses Cookies, Caramel Surprise Snickerdoodles, Mom's Coconut Snowball Kisses, Chocolate Sablés, Gingerbread Folks (with a special sturdy variation for gingerbread houses), Pecan Freezer Squares, Brownie Doughnuts, Brandy Snap Rolls. Plus 'extra special' details including homemade Dulce de Leche, Wicked Good Ganache, Lemon Curd, and more"--